STRATEGI KOMUNIKASI PEMBERDAYAAN DESA WISATA KEMIREN DALAM UPAYA MENDUKUNG SUSTAINABLE DEVELOPMENT GOALS (The Commercium, 2022)
Tourism can be development tool that aims to prosper the community. The research purpose to describe the community empowerment communication strategy carried out by Pokdarwis and other stakeholders in tourism development in Kemiren Tourism Village (case study of Kemiren Tourism Village, Banyuwangi Regency). This study also discusses the role of tourist villages as one of the tools that support the SDGs achievement which consists of 17 goals that divided into four pillars, specifically the pillars of social development, pillars of economic development, pillars of environmental development, and pillars of legal development and governance. The research was conducted using the descriptive qualitative method, and the data were obtained by in-depth interviews, field observations and social media studies that discusses Kemiren Tourism Villages. The results indicate that the effective empowerment communication strategy carried out in Kemiren Village has succeeded in effectively creating social change in the community through a tourism village development program by innovating to maximize traditional wealth and culture that is owned by creating a festival, so that tourism activities in Kemiren Village can support the SDGs achievement.